Effect of Different Musical Types on Patient’s Relaxation, Anxiety and Pain Perception during Shock Wave Lithotripsy: A Randomized Controlled Study - Çift, Ali; Benlioglu, Can (Urology Journal, 2020)
Purpose: The aim of this study was to investigate the effects of listening to different music types during extracorporeal shock wave lithotripsy (SWL) on the patients’ pain control, anxiety level, and satisfaction. Materials and Methods: This study was a prospective single-blinded, parallel-group randomized clinical trial with balanced randomization [1:1]. A total of 150 patients who underwent first-session SWL were included in the study. The patients were randomly divided in to five groups (30 participants in each group) as follows: headphones were not put on and no music was played in Group 1 (control group); headphones were put on but no music was played in Group 2; Turkish art music was listened to with headphones in Group 3; Western classical music was listened to with headphones in Group 4; thetype of music the patient liked was listened to with headphones in Group 5. Demographic data related to patients and procedure, State-Trait Anxiety Inventory-State Anxiety (STAI-SA), Visual Analog Scale (VAS) scores, willingness to repeat procedure (0: never 4: happily), and patient satisfaction rates (0: poor 4: excellent) were recorded immediately after the procedure. Results: There was a statistically significant difference between groups in terms of median VAS scores (7, 6, 4.5, 5, and 4, respectively, P<.001), whereas the VAS scores in Groups 3, 4, and 5 were significantly lower than those in Group 1 and 2 (P<.001). The median STAI-SA scores between the groups were significantly different (45, 45, 42, 45, and 40, respectively, P<.001), while the anxiety levels in Groups 3, 4, and 5 were significantly lower than those in Group 1 (P=.008, P=.018, and P<.001, respectively). Moreover, there were statistically significant differences between the groups in terms of willingness to repeat the procedure and patient satisfaction rates (P<.001). Conclusions: Music therapy during SWL reduced the patients' pain and anxiety scores, moreover listening to the patient’s preferred music type provided greater satisfaction. Listening to the patient’s preferred music type could be standardized and routinely used during SWL.